Dedicating Science and War Books: Networks of Power Between Science and Politics in the Early Modern Period - Consuelo Gómez (Journal of Early Modern Studies)
The article explores the dedications to promoters and patrons found in military and mechanical engineering books between the last decades of the sixteenth century and the first half of the seventeenth century. These dedications are significant because they show how the authors of those books managed their strategies of self-promotion within the power of the court and weaved new relationships with promoters and patrons. Through their dedications,  they attempted  to guarantee both their status as authors and that of their books.  Circulating as objects throughout elite political networks, these scientific books also enabled less tangible transactions of knowledge, prestige and power.